Advanced working system for coating ceramic workpieces with industrial robots - Khonthon, Sasithorn; Muangmeesri, Benchalak; Maneetham, Dechrit (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to use industrial robots to control the picking of ceramic cups or bowls, dip them in a glaze, and place them on a conveyor belt accurately while being able to control the speed at all times. By using industrial robots to assist in the ceramics industry, it will result in increased speed, reduced working time, and can also decrease the number of workers. Normally, dipping workpieces in an industrial factory requires manual labor to handle approximately 1000 pieces per day. Workers are prone to making mistakes while working and can experience fatigue. Therefore, robots or new technologies need to assist in industrial production. Thus, the purpose of this study is to offer product dipping. Always maintain a high standard of plating, and then deploy industrial robots. Test piece housings on a vacuum are detected by a six-axis module on an industrial robotics station. After that, the module places a test piece insert on the test piece housing after removing it from the slide. In general, the speed and location of glazing ceramics are compared to both manually and mechanically operated methods. At the end of the robot arm is a closed-loop control using a pneumatic servo valve to check the position and speed of the cup. For the system is using the PID controller with , , and the air pressure is compare with 4, 5 and 6 bar. Overall, the testing of workpiece handling control using a closed-loop servo pneumatic system will operate more accurately than an open-loop system and presents a novel approach to control system design that addresses the pneumatic servo system as a third-order time lag system. The control system with a PID controller at a pressure of 6 bar will operate the fastest and most precisely. The experiment demonstrates the effectiveness of the suggested approach. This eliminates the need for trial and error in determining that all of the proportional gain is one of the control parameters. A pneumatic servo's performance can be enhanced by achieving a greater proportional gain.